Shoshin Beriberi and Severe Accidental Hypothermia as Causes of Heart Failure in a 6-Year-Old Child: A Case Report and Brief Review of Literature - Vicinanza, Alfredo; De Laet, Corinne; Rooze, Shancy; Willems, Ariane; Beretta-Piccoli, Xavier; Vens, Daphné; Voglet, Cédric; Jacquemart, Caroline; Massin, Martial; Biarent, Dominique (Frontiers in Pediatrics, 2019)
Severe accidental hypothermia has been demonstrated to affect ventricular systolic and diastolic functions, and rewarming might be responsible of cardiovascular collapse. Until now, there have been only a few reports on severe accidental hypothermia, none of which involved children. Herein, we describe here a rare case of heart failure in a 6-year-old boy admitted to the emergency unit owing to severe hypothermia and malnutrition. After he was warmed up (core temperature of 27.2 °C at admission), he developed cardiac arrest, requiring vasoactive amines administration and veno-arterial extracorporeal membrane oxygenation. Malnutrition and refeeding syndrome might have caused the thiamine deficiency, commonly known as beriberi, which contributed to heart failure as well. He showed remarkable improvement in heart failure symptoms after thiamine supplementation. High-dose supplementation per os (500 mg/day) after reconstitution of an adequate electrolyte balance enabled the patient to recover completely within 2 weeks, even if a mild diastolic cardiac dysfunction persisted longer. In conclusion, we describe an original pediatric case of heart failure due to overlap of severe accidental hypothermia with rewarming, malnutrition, and refeeding syndrome with thiamine deficiency, which are rare independent causes of cardiac dysfunction. The possibility of beriberi as a cause of heart failure and adequate thiamine supplementation should be considered in all high-risk patients, especially those with malnutrition. Refeeding syndrome requires careful management, including gradual electrolyte imbalance correction and administration of a thiamine loading dose to prevent or correct refeeding-induced thiamine deficiency.